Disorders of Hemostasis in Overt and Subclinical Hypercortisolism - Świątkowska-Stodulska, R.; Sworczak, K. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Glucocorticoids are a group of hormones of a particular impact on hemostasis. Epidemiological studies show an approximately severalfold greater incidence of thromboembolic events in hypercortisolemic patients compared to those without hormonal disorders. The prothrombotic action of this steroid class is caused by both the direct impact of hypercortisolism on the activation of coagulation and the inhibition of fibrinolysis, as well as, the pathology of hemostasis due to metabolic disorders, which occur in this endocrinopathy. The aim of this study was to discuss the hemostasis abnormalities that occur in patients with overt and subclinical hypercortisolism with a particular emphasis on plasmatic coagulation, endogenous anticoagulation system, homocysteine and proinflammatory cytokines.
Keywords: hemostasis; coagulation; fibrinolysis; hypercortisolism; subclinical Cushing’s syndrome